IEEE International Symposium on Phased Array Systems and Technology, 2003.
DOI: 10.1109/past.2003.1257044
|View full text |Cite
|
Sign up to set email alerts
|

Phased array using the sequential rotation principle: analysis of coupling effects

Abstract: The growing demand for broadband multimedia services urges the aeronautical industry to provide bidirectional on-board communication services in near future. Today, the first aircrafts are already being equipped with the technology necessary to provide intemet access for staff and passengers. Up to now, these solutions are developed to operate in L-and Ku-Band, due to the satellite systems available and the existence of affordable RF-components for these frequency ranges. Considering broadband multimedia appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Investigations showed that this is allowed for the respective configuration because the amount of surface waves propagating is very small [6].…”
Section: °180°180°mentioning
confidence: 99%
“…Investigations showed that this is allowed for the respective configuration because the amount of surface waves propagating is very small [6].…”
Section: °180°180°mentioning
confidence: 99%
“…Some other techniques improve the cross-polarization level by rotating the antenna elements in reflectarray applications [23], or combining the 180°rotation of the antenna structure along with a 180°alternate feeding based on the overlapping of different multipolar moments [24]. Further rotation topologies such as the sequential rotation is typically used for arrays of circular polarized antennas, as it leads to an improvement of the axial ratio bandwidth or the polarization purity [25][26][27][28][29]. Generally, the majority of cross-polarization suppression techniques start from the decomposition of planar arrays into subarrays, and a very few applications consider linear arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Next to the challenge of generating high-quality circular polarization, there is the issue of side-lobe control. Regular (periodic) array antennas experience a limited frequency bandwidth due to the appearance of grating lobes and blind scan angles that are due to the element separation distance and mutual coupling [8], [9]. In addition, such arrays typically do not allow for dual-frequency operation.…”
Section: Introductionmentioning
confidence: 99%